Curcuma Significantly Boosts Weight in Underweight Toddlers in Indonesia: Temulawak Secara Signifikan Meningkatkan Berat Badan Balita dengan Berat Badan Kurang di Indonesia - Lidya Agustin Tjondro; Hesty Widowati; Paramitha Amelia Kusumawardani; Nurul Azizah (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigated the effectiveness of curcuma (Curcuma longa) in increasing the body weight of underweight toddlers. Using a Pre-Experimental One Group Pretest-Posttest design, 20 underweight toddlers from Dharma Wanita Persatuan Gebang Kindergarten and TPA Al Ma’arif Sidoarjo were given 2.5 grams of curcuma mixed with water daily for two weeks. Body weight was measured before and after the intervention. The Paired Simple T-Test analysis showed a significant increase in body weight (p = 0.000). These results suggest that curcuma is an effective intervention for increasing body weight in underweight toddlers. Highlight: Administered curcuma to 20 underweight toddlers for two weeks. Significant weight gain observed (p = 0.000). Curcuma effective for increasing toddler body weight. Keyword: Underweight, Nutritional status, Toddlers, Curcuma, Body weight